Disability outcomes of early cerebellar and brainstem symptoms in multiple sclerosis. (April 2021) - Le, Minh; Malpas, Charles; Sharmin, Sifat; Horáková, Dana; Havrdova, Eva; Trojano, Maria; Izquierdo, Guillermo; Eichau, Sara; Ozakbas, Serkan; Lugaresi, Alessandra; Prat, Alexandre; Girard, Marc; et al.
Background: Cerebellar and brainstem symptoms are common in early stages of multiple sclerosis (MS) yet their prognostic values remain unclear. Objective: The aim of this study was to investigate long-term disability outcomes in patients with early cerebellar and brainstem symptoms. Methods: This study used data from MSBase registry. Patients with early cerebellar/brainstem presentations were identified as those with cerebellar/brainstem relapse(s) or functional system score ⩾ 2 in the initial 2 years. Early pyramidal presentation was chosen as a comparator. Andersen-Gill models were used to compare cumulative hazards of (1) disability progression events and (2) relapses between patients with and without early cerebellar/brainstem symptoms. Mixed effect models were used to estimate the associations between early cerebellar/brainstem presentations and expanded disability status scale (EDSS) scores. Results: The study cohort consisted of 10, 513 eligible patients, including 2723 and 3915 patients with early cerebellar and brainstem symptoms, respectively. Early cerebellar presentation was associated with greater hazard of progression events (HR = 1.37, p  < 0.001) and EDSS (β = 0.16, p  < 0.001). Patients with early brainstem symptoms had lower hazard of progression events (HR = 0.89, p  = 0.01) and EDSS (β = −0.06, p  < 0.001). Neither presentation was associated with changes in relapse risk. Conclusion: Early cerebellar presentation is associated with unfavourable outcomes, while early brainstem presentation is associated with favourable prognosis. These presentations may be used as MS prognostic markers and guide therapeutic approach.